Retrospective study of single vitrified-warmed blastocyst transfer cycles according to the presence of morphokinetic variables - Hur, Yong Soo (Clin Exp Reprod Med, 2018)
This study retrospectively assessed whether time-lapse data relating to developmental timing and morphology were associated with clinical outcomes, with the eventual goal of using morphokinetic variables to select embryos prospectively for cryopreservation. In this study, we examined the clinical outcomes of single vitrified-warmed blastocyst transfer cycles that were cultured in a time-lapse incubation system. The morphokinetic variables included uneven pronuclei, an uneven blastomere, multinucleation, and direct, rapid, and irregular division. A total of 164 single vitrified-warmed blastocyst transfer cycles were analyzed (102 cycles of regularly developed blastocysts and 62 cycles of blastocysts with morphokinetic variables). No significant differences in the age of females or the standard blastocyst morphology were found between these two groups. The regularly developed blastocysts showed significantly higher implantation and clinical pregnancy rates than the blastocysts exhibiting morphokinetic variables (30.4% vs. 9.7% and 37.3% vs. 14.5%, respectively; p<0.01). The blastocysts that exhibited morphokinetic variables showed different mean development times compared with the regularly developed blastocysts. Although morphokinetic variables are known to have fatal impacts on embryonic development, a considerable number of embryos developed to the blastocyst stage. Morphokinetic variables had negative effects on the implantation and clinical pregnancy rates in vitrified-warmed blastocyst transfer cycles. These findings suggest that blastocysts cultured in a time-lapse incubation system should be considered for selective cryopreservation according to morphokinetic variables.